Coping with the copy-paste-syndrome - Maurer, Hermann; Kulathuramaiyer, Narayanan (Centre for Academic Information Services, UNIMAS, 2007)
The Copy-Paste Syndrome describes a situation whereby students at all levels are becoming more and more reliant on wide-range of easily-available digital content. This is a universal problem that has to be addressed effectively, especially with the revolutionary development of the Web. Weber (Weber, 2006) refers to it as the Google-Copy-Paste-Syndrome, which according to him will drastically affect the quality of scientific publications, leading to a degradation of the quality of life. The expansion of digital content together with an emerging participative social learning (and E-learning) ecosystem could result in even more devastating implications. As opportunities for the proliferation of such infringements becomes widespread, a holistic solution is required combining an institutional approach together with the application of viable technologies. This paper describes an E-learning ecosystem combined with a copy-paste detection suite to comprehensively address the emerging phenomenon.